What is culturally appropriate food consumption? A systematic literature review exploring six conceptual themes and their implications for sustainable food system transformation - House, Jonas; Brons, Anke; Wertheim-Heck, Sigrid; van der Horst, Hilje (Springer, 2024)
There is increasing recognition that sustainable diets need to be ‘culturally appropriate’. In relation to food consumption, however, it is often unclear what cultural appropriateness–or related terms, such as cultural or social acceptability–actually means. Often these terms go undefined, and where definitions are present, they vary widely. Based on a systematic literature review this paper explores how cultural appropriateness of food consumption is conceptualised across different research literatures, identifying six main themes in how cultural appropriateness is understood and applied. The paper then critically analyses these themes in relation to sustainable food system transformation. We explore how the themes conceptualise change, finding that cultural appropriateness is viewed in two main ways: either as a relatively static obstacle to be overcome, or as a dynamic and negotiated process. Both perspectives, we argue, entail different scientific, practical and political effects. Each perspective offers particular affordances for understanding and governing sustainable food system transition, although between perspectives there is likely to be a trade-off between theoretical sophistication and practical operationalizability. Based on this analysis we argue that researchers, policymakers and practitioners should be explicit about their commitment to a particular understanding of cultural appropriateness, as this will have implications for scientific and societal applications of their work. This is particularly the case, we suggest, in relation to the transdisciplinary collaborations necessary to effectively address the ‘wicked problem’ of food system sustainability. We conclude by offering a tentative general definition of cultural appropriateness as it relates to food consumption.